STRUKTUR PERAN KALIMAT TUNGGAL BERPREDIKAT VERBAL BERPREFIKS N- DALAM BAHASA BALI (The Role of a Single Sentence Structure Predicated Prefixed N- Verbal Language in Bali) - Partami, Ni Luh (SALINGKA, 2016)
This paper aims to describe the structure of a single sentence predicated verbal role N- prefixed in Balinese language. Data writing is taken from textbooks Balinese, Bali speaking story, and intuition authors as speakers of Bali. Data single sentence predicated verbal prefixed Ncollected by methods referto the technical note. Data in the form of a single sentence predicated verbal prefixed N recorded in the data card. Furthermore, the data were analyzed by the method of distributional who assisted with this reference technique and technique of substitution. Data that has been analyzed and then presented with formal and informal methods. Based on data analysis, in Balinese predicate prefixed N- which is one type of active sentence has some structure, roles, ie agentive-active, active-agentive-objective, agentiveactive-locative, agentive-active-receptive, agentive-active- benefactive-objective, agentiveactive-objective-locative, agentive-active-objective-receptive, agentive-active-receptiveobjective, agentive-active-locative-instrumental, and agentive-active-instrumental-locative.